A discussion about the Douglas-Reid model updating method and its prospective application to continuous vibration-based SHM of a historical building. (15th December 2022) - Rosati, I.; Fabbrocino, G.; Rainieri, C.
Highlight: Factors influencing model updating results by Douglas-Reid method are analyzed. Performance of continuous model updating algorithms are assessed. Robustness to the influence of varying environmental conditions is checked. Encouraging results are obtained for integration with Structural Health Monitoring. Abstract: The opportunities of Operational Modal Analysis and Finite Element model updating for non-destructive structural assessment have attracted significant research interest in recent years. In order to keep the computational efforts associated with model updating as low as possible, different strategies have been proposed over the years to approximate the model response. Among them, response surface models and the Douglas-Reid method are the most popular. However, systematic investigations about the factors affecting their model updating performance in view of Structural Health Monitoring applications are currently very limited. The present paper focuses the attention on the Douglas-Reid method, and analyzes the influence of different factors on the accuracy and reliability of model updating results. Comparisons with different updating approaches, such as grid search and the Inverse Eigensensitivity method, are also reported. The final objective is assessing the performance of the Douglas-Reid method for indirect monitoring of selected updating variables in the context of Structural Health Monitoring applications. Robustness and accuracy of model updating results under varying environmental conditions are evaluated to this aim, highlighting the interesting applicative perspectives of the method in the context of vibration-based Structural Health Monitoring, in spite of the very limited number of similar applications reported in the literature.